Optimization of starter bokashi bran from expired mushroom blocks using central composite design - Amir Syarifudin, Baharudin; Norazwina, Zainol (Universiti Malaysia Pahang, 2024)
Mushroom production as the largest solid-state fermentation industry globally. It draws attention to a significant economic and environmental challenge, specifically the storage and disposal of expired mushroom blocks (EMBs) remaining after harvest. Importance of ongoing biotechnological research focused on fungi utilizing various agro-industrial wastes to produce biofertilizer for industrial. The paper proposes using EMBs as a substrate for Bokashi fermentation as fertilizer, focusing on the development of starter Bokashi Bran. The study identifies and optimize bacterial and fungal growth in Bokashi Fermentation using ADA starter Bokashi bran sample from ADA Fresh Farm, Johor Bharu using Response Surface Methodology (RSM). Factors affecting growth both microbes were analysed: EMB content (2 g/ml to 10 g/ml) and fermentation durations (5 days to 9 days). The analysis analysed the highest bacterial and fungal growth in Starter Bokashi Bran using the Design Experts (DE) software Version 7.0 predicting maximum growth at 8 days and 4g/ml respectively. The quadratic model showed a good fit, with an R-squared value exceeding 0.80 and a confidence level surpassing 95%.The research demonstrated that EMBs can be utilized as alternative medium for starter bokashi bran that are eco-friendly and sustainable biofertilizer.